Recommendations On Nmosd Treatment In Latin America: Consensus-Based Rand/Ucla Methodology - Nicolas Alonso, Ricardo; Rivera, Visctor; German, Edgar; Contentti, Carnero; Diaz de Bedoya, Victor Fernando Hamuy; Ciampi, Ethel; Silva, Berenice; Zuluaga, Maria; Becker, Jefferson; Ignacio Rojas, Juan; Gracia, Fernando; Zarco, Luis; et al. (My University, 2023)
Introduction: Neuromyelitis optica spectrum disorder (NMOSD) is a serious condition affecting people worldwide, including Latin America (LATAM). Healthcare disparities and economic limitations make effective treatment access challenging. It is crucial to consider the best practice therapeutic decision-making, including emerging long-term preventive therapies, to ensure patients in LATAM and elsewhere can effectively manage their disease all over the world. Objectives/Aims: To establish evidence-based guidelines for treatment approaches in NMOSD patients in LATAM. A consensus process was conducted to develop validated statements. Methods: A group of NMOSD experts from LATAM utilized a 9-point Likert scale to vote on statements related to NMOSD management. The predetermined consensus threshold was set at a minimum expert agreement of 70 %. The RAND/UCLA methodology was employed to reach consensus recommendations. Results: Nineteen experts completed the consensus process between March and April 2023. In round 1, no statement failed to reach the predetermined consensus, resulting in 31 agreed statements. The statements were divided between general recommendations (14/31) and clinical scenarios (17/31). The scenarios were based on treatment-na & iuml;ve NMOSD AQP4 positive patients (4/17); treatment-naive seronegative NMOSD patients (4/17); treatment switching (5/17) and safety (4/17). Conclusions: Consensus recommendations were developed on the most important areas of NMOSD treatment by a panel of experts in LATAM. These statements are a valuable tool to guide decision-making and improve patient outcomes, serving as the foundation for developing standardized practice guidelines in our region.
Keywords: Neuromyelitis optica spectrum disorder; RAND/UCLA; Disease-modifying treatment; OPTICA SPECTRUM DISORDER; NEUROMYELITIS-OPTICA; DIAGNOSTIC-CRITERIA; EFFICACY; AZATHIOPRINE; MULTICENTER; RITUXIMAB; SAFETY